Yogyakarta Modernity Dynamics: A Study of Code-Switching in Kedaulatan Rakyats Weekly Short Stories from 2010 to 2015 - Kristanti Fransisca (Universitas Sanata Dharma, 2017)
This research analyzes how language reflects Yogyakarta modernity dynamics through the analysis of Kedaulatan Rakyats weekly short stories from 2010 to 2015. The research is aimed to find out how the citys modernity is portrayed through language by the means of code-switching in the weekly short stories. It identifies the phenomena of code-switching in the short stories and analyzes whether or not the switch is an illustration of the citys modernity through language. Keywords: code-switch, short stories, modernity, Yogyakarta.